If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5xi + -5y + 3i = 2x + 2yi + -4 Reorder the terms: 3i + 5ix + -5y = 2x + 2yi + -4 Reorder the terms: 3i + 5ix + -5y = -4 + 2iy + 2x Solving 3i + 5ix + -5y = -4 + 2iy + 2x Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2iy' to each side of the equation. 3i + 5ix + -2iy + -5y = -4 + 2iy + -2iy + 2x Combine like terms: 2iy + -2iy = 0 3i + 5ix + -2iy + -5y = -4 + 0 + 2x 3i + 5ix + -2iy + -5y = -4 + 2x Add '5y' to each side of the equation. 3i + 5ix + -2iy + -5y + 5y = -4 + 2x + 5y Combine like terms: -5y + 5y = 0 3i + 5ix + -2iy + 0 = -4 + 2x + 5y 3i + 5ix + -2iy = -4 + 2x + 5y Reorder the terms: 4 + 3i + 5ix + -2iy + -2x + -5y = -4 + 2x + 5y + 4 + -2x + -5y Reorder the terms: 4 + 3i + 5ix + -2iy + -2x + -5y = -4 + 4 + 2x + -2x + 5y + -5y Combine like terms: -4 + 4 = 0 4 + 3i + 5ix + -2iy + -2x + -5y = 0 + 2x + -2x + 5y + -5y 4 + 3i + 5ix + -2iy + -2x + -5y = 2x + -2x + 5y + -5y Combine like terms: 2x + -2x = 0 4 + 3i + 5ix + -2iy + -2x + -5y = 0 + 5y + -5y 4 + 3i + 5ix + -2iy + -2x + -5y = 5y + -5y Combine like terms: 5y + -5y = 0 4 + 3i + 5ix + -2iy + -2x + -5y = 0 The solution to this equation could not be determined.
| 8(5+5y)-2y(6+4)= | | (2x-5)+(3x-4)=-3 | | 5iz+3i=2z-4 | | i/7=4 | | 198-16= | | 15+x=15x | | 1/2+2/3= | | 17+k=9 | | xsquared+10x+10=0 | | cot^2(3x)=9 | | 109+89= | | Log(4)5=3x+5 | | 61+p=70 | | 6x+12=8x-20 | | 5.99x+5.99=11.98 | | 0=4x^2+2x-1 | | -3.6=y/8=9.2 | | 5-(2X-3)+7(X+6)= | | 7-5x=5-8x | | 5z+35+25=180 | | 6x-5=34x+32 | | 112+34+5k+4=180 | | 3x-14=2x+8 | | 86+47+5s+2=180 | | 35+110+6f+5=180 | | 114+6a+4+32=180 | | 75-50/75x100 | | 55+50+x=180 | | 3x-1=13-111 | | 2x+31=13 | | (26x+4)+(5x+2)+(30x+11)=180 | | 57+h=180 |